STUDY ON CARBON CONTENT AND ECOLOGICAL MANGROVE INDEX IN MUARAREJA, TEGAL, CENTRAL JAVA - Suyono Suyono (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2017)
The accumulation of carbon in the atmosphere causing the greenhouse effect as a result of trapping of short-wave sunlight, which increase the temperature of Earth's atmosphere. One of the forest ecosystems that can reduce the effects of greenhouse gases and to mitigate the climate change is a mangrove forest. The role of mangroves related to the Blue Carbon was emphasized as mangrove efforts to utilize CO₂ for photosynthesis and store it in biomass stock  and sediment as a climate change mitigation efforts. The purpose of the research are a) to determine the density, dominance and the importance value of mangroves index, b) to know the Diversity Index and Uniformity Index of mangrove that dominates, c) to determine the content of carbon in the mangrove forests, and d) to determine the relationship of the density of mangrove with a carbon content in the mangrove forest area in the village of Muarareja Tegal. Mangrove areas in the Village of Muarareja was dominated by Rhizophora mucronata with Relative Density (KR) in ponds: 42.11% - 100%, residential homes: 28.57% - 45.45%, the river: 31.58% - 61.90%, the beach : 59.09% - 73.68%. Relative dominance (DR) of ponds station: 34.71% - 100%, residential home stations: 14.24% - 39.61%, river station: 20.46% - 72.95%, coast stations: 64.08% - 92,25%. Importance Value Index (IVI) in ponds station: 76.82% - 200%, residential home stations: 42.81% - 85.07%, the river station: 52.03% - 134.85%, coast stations: 123.17% - 165.93%. Diversity Index (H) mangrove Rhizophora mucronata ranged by 0.000 - 0.692 and Uniformity Index (J) mangrove ranged by 0.000 - 2.107. The largest carbon content (tons / ha) was produced at the coast with the average number of total carbon content of the plot (tons / ha) was 189,942.77 tons / ha, followed by the river with the average number of total carbon content of the plot (tons / ha) was 179,011.49 tons / ha, the average number of total carbon content ot the plot for the ponds (tons / ha) was 176,519.79 tons / ha and with the average number of total carbon content of the plot (tons / ha) for the residential homes was 165,774.82 tons / ha. The density of mangrove has a very close correlation with the total carbon content in liters per hectare of the plot, the total carbon content in plants per hectare of the plot below, the total carbon content in leaves per hectare of the plot, and the total carbon content of soil per hectare of the plot. The total carbon content of the tree biomass per hectare on the plot, the total carbon content of nekromassa per hectare of the plot, and the total carbon content in the roots per hectare of the plots does not have a positive correlation with the density of mangrove.